Analysis Of The Development Of Egyptian Statehood Based On The Traditions Of Religiousness And Secularism - Malikaxon Minovvarova (Penerbit Jurnal Indonesia, 2024)
This article discusses issues such as the role of the Arab Republic of Egypt in regional and global international relations, the country's strategic location, rich cultural heritage, and balanced foreign policy, its policy aimed at creating strong regional and global alliances, attracting foreign investments, and developing trade.